The Mediating Role of Organizational Commitment between Leadership Style and Employee Job Performance - Muhammad Ali Junaid, Sadia Rafique, Mehreen Nasir, Khunsa Junaid, Iqra Junaid (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Job performance is a positive emotional condition caused by job appraisal. Poor leadership in industries causes employee dissatisfaction and turnover. Aims: To explores the relationship between transformational and transactional leadership styles and professional performance in the commercial textile sector in Lahore, Pakistan using organizational commitment as a mediator. Study design: Cross-sectional Place and duration of study: University of Lahore from 1st June 2019 to 31st December 2019. Methodology: The structured questionnaire items were answered by 300 participants on a 5-point Likert scale. Result: Most of the participants were males over 30 years and had a bachelor’s degree. Most of the respondents had more than five years of experience and were managers. The results showed that the organizational commitment of employees did have mediating effect on the relationship between transformational and transactional leadership styles and job performance. Conclusion: Organizational commitment mediates leadership style and employee performance in this study. Any organization can benefit from a leadership style that can alter with the team’s demands. A leader’s example is essential for enforcing power. Leadership must emphasize job satisfaction and long-term employee engagement to keep employees satisfied and committed. Keywords: Leadership style, Transformational leadership, Transactional leadership, Job performance,